Learning to Launch Enterprises with Open Source Code - Dehter, Mario (Ingeniería Solidaria, 2015)
This article analyzes how academic training at the engineering faculties at most Iberian-American universities is monodisciplinary, in other words, specialized in a particular technological branch, while neglecting the learning of social abilities that are basic for leadership, visionary and innovative spirits and the attitudes and aptitudes that make for good businesses. While entrepreneurial training is a topic found throughout the educational community at all levels of teaching, this does not mean that academic thinking about the difference between teaching and learning to create an enterprise should be left out. The article includes proposals to improve the quality of entrepreneurial education in engineering programs and summarizes such concepts as open source learning, flipped classroom and personal learning environment (ple). A renovation of didactic strategies is proposed for application in engineering classrooms of the components for learning to create an enterprise with open source code. Teachers must therefore deal with the risks implicit in such challenges in order to build instructional designs in which students learn and create enterprises through their own interests.